Ultra detector branula / Che Wan Kasmiza Che Wan Ahmad ... [et al.] - Che Wan Ahmad, Che Wan Kasmiza; Ismail, Norliza; Shukri, Nurul Mawaddah; Abu Hanifah, Syafawati (2018)
Peripheral intravenous cannulation is a common invasive procedure done in hospitals. Although a minor invasive procedure, it has the potential to introduce infection into the local tissue at site of cannulation or directly into the blood stream. However, due to some limitations and constraints, from this current canula, to prevent infection. Thus, in New Product Development (NPD) report, we came out with a solution to this problem which is by developing blueprint by using Ultra Detector Branula (UDB). UDB is the newly created iv canula, to facilitate the physician inserting the line in the peripheral of the child, as well as facilitate the nurse to apply during intravenous medication. Our marketing goals are in hospitals for use by doctors and nurses, specifically for children's patients. We want these targets to feel that they are going through a simpler way than ever. By suggesting and developing products, we hope we can make it easier for doctors and nurses to use them.